Progressional movement for creation Autonomous Democratic Republic of Turkestan - Agzamkhodjaev Саидакбар (Turkic Studies Journal, 2021)
This article discusses the history of the formation of an autonomous democratic republic in Turkestan, which went down in history under the name Turkiston Mukhtoriyati. It also highlights the development of the ideology of the national liberation movement, sociopolitical changes in Turkestan after February 1917, the ideological views and activities of progressives for the creation of national democratic statehood, the desire of Turkestans to self-determination of their fate, the formation of the idea of autonomy, and the involvement of the peoples of Turkestan in the autonomist movement.